Delaying the Burial of the Body of an Agam District Traditional Leader - Gafnel; Busyro Busyro; Ikhwan Ikhwan (Hakamain: Journal of Sharia and Law Studies, 2023)
This research discusses the phenomenon of delaying the burial of the customary leader of Agam Regency from the perspective of qiyas. This study uses a qualitative approach involving various data collection techniques, including interviews, participatory observation, and document analysis. Amid shifting values and changing religious practices in the community, the practice of funerals has become a sensitive issue that combines religious teachings and local traditions. A delay in the burial of a traditional leader may occur due to an important traditional ceremony or pending the arrival of family members from afar. Qiyas, as a method of analogy in Islamic law, becomes an instrument to formulate a conclusion in this case. The principle of qiyas allows postponement of burial if there is a greater benefit, such as maintaining the integrity of the family or strengthening the cultural identity of the local community. However, this must be done with due regard to basic religious principles, such as preserving the honor of the deceased and preventing any physical harm that may result from the delay. The study concludes that the postponement of the burial of the customary leader of Agam Regency from the perspective of qiyas can be justified in carefully regulated situations, considering the balance between religious demands, local traditions, and the social needs of the local community. The importance of dialogue between religious authorities and traditional leaders in addressing this issue cannot be overlooked, as it involves a deep understanding of intersecting religious and cultural values.